One year duration of immunity of a combination Bordetella bronchiseptica - canine parainfluenza oral vaccine in dogs - Wiechert-Brown, Sarah A.; Classe, Haley M.; Dant, Jennifer C.; LaFleur, Rhonda L.; Xu, Zach; Tarpey, Ian (Frontiers in Veterinary Science, 2025)
IntroductionCanine infectious respiratory disease complex (CIRDC), widely known as kennel cough or infectious tracheobronchitis, is a highly contagious disease in dogs caused by multiple bacterial and viral pathogens. Two significant pathogens that contribute to CIRDC are Bordetella bronchiseptica (B. bronchiseptica) and canine parainfluenza virus (CPI). Recently, the first oral, modified live, vaccine to contain a combination of these two pathogens has become commercially available.MethodsTo evaluate the efficacy of both fractions of this vaccine, duration of immunity studies were conducted in six- to eight-week-old beagles. In both studies, dogs were randomized into two treatment groups and vaccinated once by the oral route with either test vaccine or placebo vaccine. In the CPI study, dogs were challenged with virulent CPI one year after vaccination and observed daily for 14 days post-challenge. Nasal swabs were also collected daily for 10 days post-challenge to evaluate the shedding of the challenge virus. In the B. bronchiseptica study, dogs were challenged with virulent B. bronchiseptica one year after vaccination and observed twice daily for 28 days post-challenge for clinical signs of disease.ResultsThe results from these studies demonstrated a significant reduction in nasal shedding of CPI (0.2 log10FAID50/mL in test-vaccinated compared to 1.1 log10FAID50/mL in placebo-vaccinated dogs) as well as a significant reduction in clinical signs associated with B. bronchiseptica (9% of test-vaccinated compared to 74% of placebo-vaccinated dogs).ConclusionTaken together, these studies demonstrated that oral vaccination with a combination vaccine containing B. bronchiseptica and CPI is effective at preventing disease for at least one year following vaccination.